Pengaruh Current Ratio, Debt to Equity Ratio, dan Devidend Pay Out Ratio terhadap Price Earning Ratio pada Kelompok Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia - Sunaryo Sunaryo (Bina Nusantara University, 2011)
The primary objectives of this research is to learn correlation and effecting among CR, DER, and DPR with PER neither partial nor simultaneous. Data secondary collected by industrial random sampling groups listed at IDX and the journal preceding research persons. The results of the research describe that CR and DER have not any effecting significant, negative medium correlation for CR, and negative high correlation to PER, and DPR have effecting significant, positive low correlation to PER. But CR, DER, and DPR have the effecting significant simultaneous to PER. Recommended that the topic of this research can be continued with merchandising company groups, or service company groups either general or special service company groups likely banking, hotel, or insurance, or added with new independence variables.